Relationship between albumin-corrected anion gap and lumbar spine bone mineral density: a cross-sectional study - Aiguo Liu; Aiguo Liu; Ting Ying; Shuang Deng; Chenxu Wang; Chenxu Wang; Ziwen Zhao; Sitong Zhang; Han Xiao; Chengqing Yi; Dejian Li (Frontiers in Aging)
ObjectivesThis study aimed to investigate the relationship between albumin-corrected anion gap (ACAG) and lumbar spine bone mineral density (BMD) in a diverse population, assessing how variations in ACAG levels correlate with changes in lumbar spine BMD and the potential implications for osteoporosis risk.MethodsA cross-sectional analysis was conducted involving 3,057 participants (1,555 males and 1,502 females). Participants were stratified into quartiles based on baseline ACAG levels. Demographic and clinical characteristics were analyzed, including age, sex, education level, body mass index (BMI), and prevalence of diabetes and hypertension. The association between ACAG and lumbar spine BMD was evaluated using multiple regression models, and a generalized additive model was employed to identify potential nonlinear relationships.ResultsThe analysis revealed a significant negative correlation between ACAG and lumbar spine BMD (P < 0.001). For each 1-unit increase in ACAG, BMD decreased with β coefficients of −0.004 to −0.005 across various models. Quartile analysis indicated that participants in the highest ACAG quartile (≥19.55) experienced the most substantial reductions in BMD (β coefficients ranging from −0.034 to −0.036, P < 0.001). Furthermore, a U-shaped relationship was identified, with a turning point at an ACAG value of 22.15, indicating that lower ACAG levels were associated with decreased BMD, while higher levels showed a positive effect. Subgroup analyses by sex demonstrated consistent findings, with significant associations in both males and females.ConclusionThe findings underscore a significant association between elevated ACAG levels and reduced lumbar spine BMD, suggesting that ACAG may serve as a valuable biomarker for assessing osteoporosis risk. The identified nonlinear relationship further emphasizes the complexity of metabolic influences on bone health. These results warrant further investigation into the mechanisms underlying ACAG’s impact on bone density and its potential role in osteoporosis prevention strategies.